A modern termelésirányítás nyugati modelljeinek magyar recepciója 1945 előtt - Stausz, Péter (Közép-Európai Közlemények, 2014)
It is always an important question to the Hungarian social scientists, whether Western patterns and strategies become known simultaneously or with some delay in Hungary. It is the also case with the modern management science theories founded by Frederick Winslow Taylor and management practices developed by Henry Ford. This study focuses on their Hungarian theoretical reception before the end of Second World War answering the question has been put above. Presenting the wide professional debate on Taylorism in the circles of Association of Hungarian Engineers and Architects in 1912 it can be stated that Taylor’s concept was commonly known among Hungarian engineers managing large scale industries. They had balanced and well(based view on Taylorism and the limits of implementing its findings in the field of economy and public service. During the 1920’s more light was shed to Ford’s activities which received mostly favourable reception from Hungarian experts. Thus it can be stated that Taylor’s and Fords’s concepts became known with only a minimal delay in Hungary and the Hungarian scientific circles strived for forming a balanced critique on them.